2010
DOI: 10.1520/jai102543
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hydrogen on Rolling Contact Fatigue Response of Rolling Element Bearings

Abstract: It is generally accepted that the rolling contact fatigue (RCF) life of bearing components is strongly reduced when the hardened steel matrix contains hydrogen. Although frequently reported in the literature, a physically sound explanation to this phenomenon has not yet been presented. In recent work on building understanding around the nature of the RCF damage process, we have reported on the development of a physically based fatigue damage model. Here we discuss an attempt to interpret the role of hydrogen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 25 publications
2
55
0
Order By: Relevance
“…near surface), nor locally where hydrogen is attracted at traps such as crack tips [28,60], areas of plastic deformation and inclusions [14]. It is likely the concentration at these locations will be higher due to hydrogen being attracted and trapped at these sites [28,29,60].…”
Section: Thermal Desorption Analysis (Tda)mentioning
confidence: 99%
See 4 more Smart Citations
“…near surface), nor locally where hydrogen is attracted at traps such as crack tips [28,60], areas of plastic deformation and inclusions [14]. It is likely the concentration at these locations will be higher due to hydrogen being attracted and trapped at these sites [28,29,60].…”
Section: Thermal Desorption Analysis (Tda)mentioning
confidence: 99%
“…It is, however, noted that trapping and saturation of cracks with hydrogen could eventually lead to an internal pressure buildup stimulating crack growth. A counter-argument to this is that saturation of the crack could alleviate the ability for crack face rubbing/beating to occur during RCF [28], where crack rubbing/beating is proposed to generate WEAs [28,29]. It is suggested that in the formation process of WEAs, hydrogen serves only to enhance brittle cracking, forcing cracks open and inducing additional crack rubbing/beating [28].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations